190k views
2 votes
How can you prove that csc^2 θtan^2 θ-1=tan^2 θ?

1 Answer

9 votes


\stackrel{\textit{Pythagorean Identities}}{1+tan^2(\theta)=sec^2(\theta)}\implies tan^2(\theta ) = sec^2(\theta )-1 \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ csc^2(\theta )tan^2(\theta )-1~~ = ~~tan^2(\theta ) \\\\[-0.35em] ~\dotfill


csc^2(\theta )tan^2(\theta )-1\implies \cfrac{1}{sin^2(\theta )}\cdot \cfrac{sin^2(\theta )}{cos^2(\theta )}-1\implies \cfrac{1}{cos^2(\theta )}-1 \\\\\\ \cfrac{1^2}{cos^2(\theta )}-1\implies \left[ \cfrac{1}{cos(\theta )}\right]^2-1\implies sec^2(\theta )-1\implies tan^2(\theta )

User Sergii Rudchenko
by
5.2k points